The impact of corruption factor on investment attractiveness of the countries of Southeast Asia - V. A. Sukhanov (Международная аналитика, 2016)
The author considers the mechanisms of corruption impact on institutional attractiveness of the countries of Southeast Asia. It is argued that investors not so much incur financial losses as suffer from indeterminacy and lack of awareness in the future of their business due to corruption. The paper also suggest an assessment of corruption levels in various SEA countries and characterizes practices of anti-corruption activities, especially successful in Singapore, where business and investment climate is considered to be one of the best in the world. Special attention is also paid to future prospects of Russian business in SEA.